The Influence of Various Morphologic and Hemodynamic Carotid Plaque Characteristics on Neurological Events Onset and Deaths. (2009) - Brajović, Milan D.; Marković, Nataša; Lončar, Goran; Šekularac, Nikola; Kordić, Dejan; Despotović, Nebojša; Erceg, Predrag; Donfrid, Branislav; Stefanović, Zvezdan; Bajčetić, Milica; Brajović, Ljiljana; Savić, Živorad
Abstract : A group of 72 patients with 111 asymptomatic carotid stenoses (ACS), mean age 65.42 ± 9.21, and a group of 36 patients with 58 symptomatic carotid stenoses (SCS), mean age 67.63 ± 8.79, were analyzed prospectively during a 3-year follow-up period. All patients underwent color duplex scan sonography (CDS), carotid arteriography, computed tomography (CT) scan, and neurological examination. The aim of the study was to analyze the correlation between echo plaque morphology (degree and plaque quality), local hemodynamic plaque characteristics, ischemic CT findings, and onset of new neurological events and deaths. The results analysis showed significantly more ACS in the group of 30–49% stenosis ( p < 0.001), but significantly more SCS in the group of 70–89% ( p < 0.0001) and ≥90% stenosis ( p < 0.05). Fibrous plaque was more frequent in the ACS group ( p < 0.001), while ulcerated and mixed plaques were more frequent in the SCS group (both p < 0.0001). In the SCS group, a significantly higher frequency of increased peak systolic and end diastolic velocities was noted at the beginning and end of the study (both p < 0.01), as well as for contralateral common (CCA) or internal carotid artery (ICA) occlusion ( p < 0.05 and p < 0.01, respectively), but reduced carotid blood flow volume ( p < 0.05) only at the end of the study. In the ACS group, the best correlation with new neurological events and deaths was shown with positive CT findings, peak systolic flow velocity over 210 cm/sec, end diastolic flow velocity over 110 cm/sec, plaque stenosis ≥70%, plaque ulceration, mixed plaque (all p < 0.0001); stenosis ≥50% ( p < 0.001); and reduced carotid blood flow volume ( p < 0.05).